Economic Development and the Theory of International Trade - Findlay, Ronald (American Economic Review, 1979)
Recently the major issue in the international aspects of economic development has been the so-called dialogue in connection with the UN resolutions calling for a New International Economic Order. The intellectual basis for the proposed reforms, in so far as one exists, appears to lie in the well-known writings of Raul Prebisch and Hans Singer. Both of them argue that there is a fundamental asymmetry in the workings of the global economic system which biases the resulting income distribution in favor of the industrial North and against the predominantly primary producing South. Neither writer has been successful in putting forward convincing arguments for such asymmetry. The standard trade theory of the HeckscherOhlin variety is usually presented in such a way that countries A and B are identical in all respects except for a difference in factor proportions that leads to pretrade product and factor-price differentials that are removed by free trade. There is no room for any asymmetry here. It would therefore seem to be both relevant and interesting to construct and investigate models that exhibit the PrebischSinger asymmetry at the level of rigor that generally prevails in pure trade theory. The rest of this paper will present two examples of such models from current research. The first consists of a simple diagrammatic exposition of an interesting but heavily mathematical paper by Murray Kemp and M. Ohyama and the second outlines the essential features of an approach to the analysis of North-South economic relations found in my earlier paper. 1. The Kemp-Ohyama Model